Analisis Penilaian Kinerja pada Organisasi Sektor Publik (Systematic Literature Review) - Kurniasari Tripambudi (SMARTINDO, 2022)
Purpose of this article:This article aims to briefly describe performance evaluation tools which is applied or used by public sector oranizations.Methodology: The method used is systematic literature to identify, describe, and classify some result of research about performance evaluation tools in public sector organizations.Result: Every organizations and nations has a different method or technique in assessing their employee performance, especially to public sector organization